The Effect of Domicile Distance on Employee Performance - Dede, Dede Sulaeman; Farhan, Akhmad; Winanti (International Journal of Innovation Research in Education, Technology and Management, 2025)
The variable of domicile distance is often ignored and considered not very important in its impact on employee performance in a company. This study aims to find out whether there is an effect of domicile distance on employee performance. This study uses a quantitative approach. The sample of this study uses a nonprobability sampling technique with random sampling, the sample of this study is 77 people who work at PT. ISS Indonesia. Data collection used a questionnaire which was then processed by the analysis method of validity and reliability test, correlation coefficient, determination coefficient and t-count test (partial test) using SPSS version 26.0. The results of this study show that the distance of domicile has no effect on employee performance, the distance of domicile and employee performance has a positive relationship but the level of relationship is very low, which is only 1.8%.